The Role of Self Efficacy Towards Mathematical Problem Solving Ability in Terms of Positive Thinking Ability - Yuliyani, Rahmawati; Handayani, Shinta Dwi; Somawati, Somawati (Department of Mathematics, Universitas Negeri Semarang, 2017)
This research aims to know the influence of the role of self efficacy towards solving math problems in terms of positive thinking. The method used was survey methods with quantitative approach and hypothesis testing using path analysis. Large sample as many as 140 students, with sampling the sampling technique used was saturated. The results of hypothesis testing indicate that: 1) there is a significant direct influence on self efficacy against the ability of solving math problems, with the line coefficient of 0.187 and contribute directly towards the ability of self efficacy the mathematical problem solving of 3.50%. 2) there are no significant direct influence positive thinking towards mathematical problem solving ability, with the line coefficient of 0.034 and direct contribution towards positive thinking ability of solving math problems very small even barely contribute, only amounted to 0.12%. 3) there is a significant direct influence on self efficacy against positive thinking, with a coefficient of line of direct contributions and 0.181 self-efficacy (self efficacy) toward positive thinking of 3.27%. 4) there were no significant effects of self efficacy against mathematical problem solving ability through positive thinking, with the line coefficient of 0.006.